Dermatologic Conundrum: A Cardiac Condition Masqueraded as a Dermatologic Distraction - George Degheim; Evan Hiner; Abeer Berry; Nathan Foster (Case Reports in Infectious Diseases)
A 38-year-old male presented to the emergency department (ED) complaining of extreme pain and a petechial rash on the left ankle for two weeks associated with generalized fatigue, intermittent fevers, and weight loss. He was discharged home from the ED on pain medications. He returned a few days later with a progressive rash that involved the entire left lower extremity to the level of the knee. He was diagnosed with herpes zoster (shingles) and was prescribed acyclovir and steroids. After several days, the patient presented for the third time to the ED. He developed a right lower extremity discomfort this time. The pain in bilateral lower extremities had become unbearable. His cardiac examination revealed a systolic murmur at the apex and a faint diastolic murmur at the left sternal border. Ultimately, he had an echocardiogram that demonstrated both a bicuspid aortic valve and large vegetation on the anterior leaflet of the mitral valve, and his blood culture grew Streptococcus mitis and Streptococcus oralis. The patient was subsequently diagnosed with subacute bacterial endocarditis thought to be sourced from his poor dentition. The diagnosis of infective endocarditis is often delayed due to its nonspecific clinical presentations. Our case displays an unusual skin manifestation of IE that may be present in the absence of other signs and symptoms of the disease.